2018
DOI: 10.3389/fpls.2018.00703
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Drought and Plant Genotype Change Epidemiological Traits of Cauliflower mosaic virus

Abstract: Plants suffer from a broad range of abiotic and biotic stresses that do not occur in isolation but often simultaneously. Productivity of natural and agricultural systems is frequently constrained by water limitation, and the frequency and duration of drought periods will likely increase due to global climate change. In addition, phytoviruses represent highly prevalent biotic threat in wild and cultivated plant species. Several hints support a modification of epidemiological parameters of plant viruses in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 59 publications
3
49
1
Order By: Relevance
“…In the case of SMV, accumulation was reduced in soybean plants experiencing a severe water deficit, while viral infection increased significantly under water-saturated conditions [57]. Similarly, CaMV accumulation was reduced in several A. thaliana accessions subjected to water deficit [52]. Moreover, under these conditions, disease appearance and development were negatively affected, likely due to a slower systemic movement and the long-distance transport of viral particles through phloem [52,94].…”
Section: Alteration Of Viral Traits Under Abiotic Stressesmentioning
confidence: 98%
See 2 more Smart Citations
“…In the case of SMV, accumulation was reduced in soybean plants experiencing a severe water deficit, while viral infection increased significantly under water-saturated conditions [57]. Similarly, CaMV accumulation was reduced in several A. thaliana accessions subjected to water deficit [52]. Moreover, under these conditions, disease appearance and development were negatively affected, likely due to a slower systemic movement and the long-distance transport of viral particles through phloem [52,94].…”
Section: Alteration Of Viral Traits Under Abiotic Stressesmentioning
confidence: 98%
“…In recent years, there have been some reports on the effects of other abiotic factors, namely CO 2 , O 3 , and water stress, on the spread of viral diseases as a consequence of the extreme environmental changes [48,[51][52][53][54][55][56][57][58]. Dader and colleagues [53] thoroughly examined the impact of elevated CO 2 levels (eCO 2 ) on M. persicae life history, feeding behaviour, and the virus transmission ability of Cucumber mosaic virus (CMV; cucumovirus) to pepper plants (Capsicum annuum), transmitted in a non-circulative manner.…”
Section: Impact Of Abiotic Stresses On Viral Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although global GM crop regulations vary widely (see discussion above), canola is a good example of a common GM crop that can also be infected by CaMV. It has recently been shown that water stress can influence CaMV virulence and transmission: under wellwatered conditions, viral load, virulence, and transmission rate increased, whereas under water deficit, transmission rate, and virulence decreased (Bergès et al, 2018).…”
Section: Camv In Agriculture and Management Practices To Reduce Camv mentioning
confidence: 99%
“…Yet studies rarely measure the responses of plants to multiple stresses and even fewer studies have quantified the molecular mechanisms and ecological outcomes of tripartite plant-vector-pathogen interactions in the context of drought. However, the potential for non-additive effects of multiple stresses has contributed to a growing consensus that simplified investigations of pairwise interactions may not be sufficient (Mittler and Blumwald, 2010;Atkinson and Urwin, 2012;Atkinson et al, 2013;Prasch and Sonnewald, 2013;Bergès et al, 2018). Thus, the goal of this review is to outline the current state of the field and synthesize research on responses of drought-stressed plants to pathogen and herbivore attack.…”
Section: Introductionmentioning
confidence: 99%